Mixing of d(x)(-y)(2)(2) and d(xy) superconducting states for different filling and temperature - Ghosh, A.; Adhikari, S. K. (Elsevier B.V., 2002)
We investigate the solution of the gap equation for mixed order parameter symmetry states as a function of filling using a two-dimensional tight-binding model incorporating second-neighbor hopping for tetragonal and orthorhombic lattice, the principal (major) component of the order parameter is taken to be of the d(x2-y2) type, As suggested in several investigations the minor component of the order parameter is taken to be of the d(xy) type. Both the permissible mixing angles 0 and pi/2 between the two components are considered. As a function of filling pronounced maxima of d(x2-y2) order parameter is accompanied by minima of the d(xy) order parameter. At fixed filling. The temperature dependence of the two components of the order parameter is also studied in all cases. The variation of critical temperature T, with filling is also studied and T-c is found to increase with second-neighbor hopping. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: mixed-symmetry state; high-T-c superconductor; d(x2)-(y2) and d(xy) order parameters